Beyond “women and youth”: Applying intersectionality in agricultural research for development - Tavenner, Katie; Crane, Todd A. (SAGE Publications, 2019)
“Women and youth” targets are commonly homogenized both in development discourse and in programmatic targeting. While this framing aims to recognize the customary inequities in agricultural development activities traditionally oriented toward elder men, the homogenization of these categories does not capture the intra-gender differences between these social groups. We explore the utility of intersectionality as an applied analytic concept in agricultural research for development to shed light on the heterogeneity of these social groups and the gender power relations that mediate farmer engagement with agriculture. Drawing on qualitative interview data from the Tanzanian dairy sector, this study applies intersectional analysis to explore how gender, generation, and marital status create power relationships that influence farmers’ positioning to engage in dairy production, institutions, and processes. We find that applying intersectionality helps us understand not only intersecting inequalities but also the fundamentally different experiences and power outcomes that occur at these intersections.